Digital: real hope or a new drama for Africa? [Mbaye Fall Diallo] - (:unkn) unknown (My University, 2023)
Xerfi Canal interviewed Mbaye Fall Diallo, university professor at IAE Lille, about digital for Africa.An interview conducted by Jean-Philippe Denis.
Keywords: African Research